Complex method of video stream intensity control - Tverdokhleb, V.; Barannik, V.; Himenko, V.; Kovalevskiy, S.; Warwas, K.; Brocki, M. (Springer Nature Switzerland AG, 2020)
Consider the construction of a video stream bit rate controlling method, based on the non-equilibrium positional coding of a transformants bit representation. Developed the concept of combined use of technologies, which allows to adapt the video data intensity to the channel bandwidth in the conditions of its dynamic change.
Keywords: DCT transformant; Transformants bit representation; Bit plane; Video stream intensity; Bandwidth